New Results on Exponential Stability of Fractional Order Nonlinear Dynamic Systems - Li, Tianzeng; Wang, Yu; Yang, Yong (Discontinuity, Nonlinearity, and Complexity, 2026)
In this letter stability analysis of fractional order nonlinear systems is studied. An extension of Lyapunov direct method for fractional order systems is proposed by using the properties of Mittag-Leffler function and Laplace transform. Some new sufficient conditions which ensure local exponential stability of fractional order nonlinear systems are proposed firstly. And we apply these conditions to the Riemann-Liouville fractional order systems by using fractional comparison principle. Finally, three examples are provided to illustrate the validity of the proposed approach.